2008
DOI: 10.1099/jmm.0.2008/002444-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum and whole-blood specimens for the detection of Candida DNA in critically ill, non-neutropenic patients

Abstract: In contrast to the multitude of studies on fungal PCR assay methods, little work has been reported evaluating Candida PCR performance when using whole blood compared with serum in candidaemic patients. Here, a comparison of the performance of whole-blood and serum specimens using a set of real-time PCR Candida species assays is described. Specimens were collected prospectively from non-neutropenic adults who were recruited to a diagnostic clinical trial, the primary purpose of which was to verify the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 17 publications
(8 reference statements)
2
12
0
Order By: Relevance
“…Although small numbers of paired samples were tested, we detected Candida DNA more often in serum (71%) and plasma (75%) than in whole blood (56%) (Fig. 1), as has been observed in other studies (1,14,23). It has been demonstrated in rabbit models that free DNA (in the serum and plasma fractions) is cleared more slowly than intracellular DNA, and the efficiency of extraction of fungal DNA from plasma or serum is higher than that from whole blood (1,14).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Although small numbers of paired samples were tested, we detected Candida DNA more often in serum (71%) and plasma (75%) than in whole blood (56%) (Fig. 1), as has been observed in other studies (1,14,23). It has been demonstrated in rabbit models that free DNA (in the serum and plasma fractions) is cleared more slowly than intracellular DNA, and the efficiency of extraction of fungal DNA from plasma or serum is higher than that from whole blood (1,14).…”
Section: Discussionsupporting
confidence: 53%
“…The sensitivity of DNA detection may also vary with the time of blood sampling during the course of the infection (23). MT-PCR was more likely to be positive when it was performed with whole blood collected within Ϯ24 h of T ϭ 0 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DNA release in blood fractions showed that most DNA is found in a cell-free form that remains in the plasma fraction after whole-blood centrifugation (204). Interestingly, clinical studies comparing PCR analysis of serum with that of whole blood or plasma found that PCR on whole blood is significantly less sensitive than PCR on the other two types of specimens (195,200). This observation can be explained by the cumbersome purification and cell lysis steps associated with the use of whole blood for DNA extraction, which may decrease sensitivity by destroying some of the free circulating fungal DNA.…”
Section: Pcrmentioning
confidence: 99%
“…Multiple studies have evaluated the performance of PCR tests for the diagnosis of invasive Candida infections in patient populations (4,118,(185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202) (studies are summarized in Table 5). The ranges of reported sensitivity and specificity values are 56.2 to 100% and 54 to 100%, respectively.…”
Section: Pcrmentioning
confidence: 99%
“…For PCR assessment of invasive aspergillosis, whole blood was claimed to be superior to plasma [52], but for the detection of invasive candidiasis, serum specimens were described to be preferable to whole blood [53]. This example illustrates the current lack of firm knowledge regarding the appropriate selection of clinical materials providing the most suitable source for timely molecular diagnosis of IFI.…”
Section: Towards Molecular Diagnostics Of Invasive Fungal Infectionsmentioning
confidence: 99%